2016
DOI: 10.1007/s11012-016-0436-9
|View full text |Cite|
|
Sign up to set email alerts
|

Taguchi design of three dimensional simulations for optimization of turbulent mixed convection in a cavity

Abstract: This study discusses the application of Taguchi method in assessing maximum heat transfer rate for the turbulent mixed convection in an enclosure embedded with rotating isothermal cylinder. The simulations were planned based on Taguchi's L16 orthogonal array with each trial performed under different conditions of position of the cylinder, Reynolds number (Re) and Rayleigh number (Ra). The thermal lattice Boltzmann based on D3Q19 methods without any turbulent submodels was purposed to simulate the flow and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Two different forms of double MRT thermal LBM have been utilized by researchers, namely Fallah al. [9], Esfahani et al [10], to improve the numerical stability. Significantly improved the numerical stability of the thermal lattice Boltzmann models.…”
Section: Introductionmentioning
confidence: 99%
“…Two different forms of double MRT thermal LBM have been utilized by researchers, namely Fallah al. [9], Esfahani et al [10], to improve the numerical stability. Significantly improved the numerical stability of the thermal lattice Boltzmann models.…”
Section: Introductionmentioning
confidence: 99%
“…Fallah et al 9 investigated 3D two-phase nanofluid natural convection in a cavity using Lattice Boltzmann Model and optimized with Taguchi approach. Alinejad et al 10 numerically studied 3D turbulent fluid flow and combined heat transfer in an enclosure using Lattice Boltzmann Model and optimized with Taguchi design. Esfahani et al 11 investigated 3D natural convection around the pipe using Lattice Boltzmann Model and optimized with Taguchi method.…”
Section: Introductionmentioning
confidence: 99%
“…Research has been conducted on tolerance design optimization for robust design using the Taguchi method. The Taguchi method [7][8][9] is an experimental design technique that helps to design an efficient and cost-effective experiment. Rout et al [10] identified kinematic and dynamic parameter tolerance combinations and selection of optimum tolerance specifications by using the Taguchi method.…”
Section: Introductionmentioning
confidence: 99%